Electrochemical Investigations of the Anticancer Drug Idarubicin Using Multiwalled Carbon Nanotubes Modified Glassy Carbon and Pyrolytic Graphite Electrodes. Issue 6 (9th May 2013) - Kurbanoglu, Sevinc; Dogan‐Topal, Burcu; Uslu, Bengi; Can, Alp; Ozkan, Sibel A.
Abstract The effect of surface modifications on the electrochemical behavior of the anticancer drug idarubicin was studied at multiwalled carbon nanotubes modified glassy carbon and edge plane pyrolytic graphite electrodes. The surface morphology of the modified electrodes was characterized by scanning electron microscopy. The modified electrodes were constructed for the determination of idarubicin using adsorptive stripping differential pulse voltammetry. The experimental parameters such as supporting electrolyte, pH, accumulation time and potential, amount of carbon nanotubes for the sensitive assay of idarubicin were studied as details. Under the optimized conditions, idarubicin gave a linear response in the range 9.36×10−8–1.87×10−6 M for modified glassy carbon and 9.36×10−8–9.36×10−7 M for modified edge plane pyrolytic graphite electrodes. The detection limits were found as 1.87×10−8 M and 3.75×10−8 M based on modified glassy carbon and edge plane pyrolytic graphite electrodes, respectively. Interfering species such as ascorbic acid, dopamine, and aspirin showed no interference with the selective determination of idarubicin. The analyzing method was fully validated and successfully applied for the determination of idarubicin in its pharmaceutical dosage form. The possible oxidation mechanism of idarubicin was also discussed. The results revealed that the modified electrodes showed an obvious electrocatalytic activity toward the oxidation of idarubicin by a remarkable enhancement in the current response compared with bare electrodes.